2019
DOI: 10.1101/513192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

All-optical interrogation of a direction selective retinal circuit by holographic wave front shaping

Abstract: Direction selective (DS) ganglion cells (GC) in the retina maintain their tuning across a broad range of light levels. Yet very different circuits can shape their responses from bright to dim light, and their respective contributions are difficult to tease apart. In particular, the contribution of the rod bipolar cell (RBC) primary pathway, a key player in dim light, is unclear. To understand its contribution to DSGC response, we designed an all-optical approach allowing precise manipulation of single retinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Since multiplane TF is a relatively new technology, few biological applications have been reported so far: 3D-SHOT was used to mimic a sensory stimulus 96 . MTF-CGH was used to investigate the contribution of rod bipolar cells to the response of direction selective ganglion cells in the retina 99 . These biological experiments were all performed in superficial cortical layers or using in vitro preparations.…”
Section: Multiplane Temporal Focusingmentioning
confidence: 99%
“…Since multiplane TF is a relatively new technology, few biological applications have been reported so far: 3D-SHOT was used to mimic a sensory stimulus 96 . MTF-CGH was used to investigate the contribution of rod bipolar cells to the response of direction selective ganglion cells in the retina 99 . These biological experiments were all performed in superficial cortical layers or using in vitro preparations.…”
Section: Multiplane Temporal Focusingmentioning
confidence: 99%
“…Given the graded, non-spiking membrane properties of most interneurons, the application of this method to retinal circuitry is likely to be successful. Indeed, a preprint describing this approach in retina indicates that one can stimulate hundreds of rod BCs while measuring responses in a field of RGCs expressing genetically encoded calcium indicators (Spampinato et al, 2019 ).…”
Section: Genetically Encoded Optical Tools To Gain Insightmentioning
confidence: 99%
“…Several studies have shown that it is possible to cluster cells in different homogeneous types [ 5 ]. This can be done using either the responses of each cell to several standard stimuli [ 6 8 ], or using genetic tools [ 9 , 10 ]. These methods have proven successful in isolating most cell types in the retina [ 7 , 11 , 12 ] and there are several ongoing studies trying to apply these approaches in the cortex [ 13 ].…”
Section: Introductionmentioning
confidence: 99%